Impact of COVID-19 Pandemic on Paediatric Trainees in Belgium - Tine Alliet; Thomas Gestels; Siel Daelemans; Levi Hoste (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Background and objectives: The COVID-19 pandemic has put strain on the activities and well-being of health care workers. We aimed to measure the direct and indirect impact on a personal and professional level for paediatric trainees in Flanders, Belgium.Study design: Junior representatives of the Flemish Society for Paediatrics (Jong VVK) conducted a longitudinal study among their fellow paediatric trainees. The impact of COVID-19 on daily tasks, education and emotional well-being for the first (March-April 2020) and second wave (October-November 2020) of the pandemic were studied.Results: One hundred and nineteen surveys were completed in the first wave, representing data of 51% (119/233) of the total number of paediatric trainees in Flanders. Eighty surveys were completed in the second wave. Educational program changes occurred in 25% (30/119) of trainees and more than half (61%; 72/119) described the pandemic as an impediment for their educational progress. The perception of impaired education persisted for 30% of the responders (24/80) during the second wave. One out of three (30%; 35/119) felt their job was more exhausting than usual and 38% (45/119) perceived more stress at work. These numbers were comparable at both time points. Increases in stress paralleled with increased irritability in daily life and poorer sleep quality. Conclusions: COVID-19 had an important impact on the daily tasks, education and emotional well-being of the paediatric trainees. Medical training centres should be aware that there is a perception of impediment on the educational program of the paediatric trainee.